2020
DOI: 10.3390/cells9061358
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]-NODAGA-RGD Positron Emission Tomography (PET) for Assessment of Post Myocardial Infarction Angiogenesis as a Predictor for Left Ventricular Remodeling in Mice after Cardiac Stem Cell Therapy

Abstract: Angiogenesis plays a central role in the healing process following acute myocardial infarction. The PET tracer [68Ga]-NODAGA-RGD, which is a ligand for the αvβ3 integrin, has been investigated for imaging angiogenesis in the process of healing myocardium in both animal and clinical studies. It’s value as a prognostic marker of functional outcome remains unclear. Therefore, the aim of this work was to establish [68Ga]-NODAGA-RGD for imaging angiogenesis in the murine infarct model and evaluate the tracer as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…RGD-based imaging of myocardial infarction observed consistent findings from studies of rats, specific RGD tracer accumulation uptake increased in vivo corresponding to infarcted and peri-infarct myocardial regions, and decreased after reperfusion (167)(168)(169)(170). Tracer uptakes were expected to be used to monitor the process of myocardial repair (171)(172)(173). Makowski et al confirmed the feasibility of 18 F-Galacto-RGD to monitor vascular remodeling during evolving MI in human studies; tracer uptake was significantly correlated with infarct size and impairment of myocardial blood flow (174).…”
Section: Conclusion and Other Perspectivesmentioning
confidence: 97%
See 1 more Smart Citation
“…RGD-based imaging of myocardial infarction observed consistent findings from studies of rats, specific RGD tracer accumulation uptake increased in vivo corresponding to infarcted and peri-infarct myocardial regions, and decreased after reperfusion (167)(168)(169)(170). Tracer uptakes were expected to be used to monitor the process of myocardial repair (171)(172)(173). Makowski et al confirmed the feasibility of 18 F-Galacto-RGD to monitor vascular remodeling during evolving MI in human studies; tracer uptake was significantly correlated with infarct size and impairment of myocardial blood flow (174).…”
Section: Conclusion and Other Perspectivesmentioning
confidence: 97%
“…RGD-based imaging of myocardial infarction observed consistent findings from studies of rats, specific RGD tracer accumulation uptake increased in vivo corresponding to infarcted and peri-infarct myocardial regions, and decreased after reperfusion ( 167 – 170 ). Tracer uptakes were expected to be used to monitor the process of myocardial repair ( 171 173 ). Makowski et al.…”
Section: Conclusion and Other Perspectivesmentioning
confidence: 99%
“…To date, two 68 Ga-based PET tracers have reached FDA approval and utilize 68 Ga provided predominantly from the generator; the comparably large elution volumes require fractionation and concentration of the eluted activity using ion-exchange chromatography to ascertain high molar activity (MA) radiolabeling in solution. 44,45 Following radiolabeling, the product is further puried with solid phase extraction to remove unbound 68 Ga. These steps are both time consuming and can lead to additional loss of radioactivity during separation and transfer.…”
Section: Optimized Radiolabeling With 68 Gamentioning
confidence: 99%
“…Lang et al had previously demonstrated the effectiveness of their cardiac induced cells (CiC) transplant in promoting angiogenesis [56]. They decided to test the effectiveness of the [ 68 Ga]-NODAGA-RGD in a mouse model of myocardial infarction.…”
Section: Angiogenesismentioning
confidence: 99%